2010
DOI: 10.4012/dmj.2009-073
|View full text |Cite
|
Sign up to set email alerts
|

Improved brushing durability of titanium dioxide coating on polymethyl methacrylate substrate by prior treatment with acryloxypropyl trimethoxysilane-based agent for denture application

Abstract: The purpose of this study was to determine whether the brushing durability of a titanium dioxide coating on a polymethyl methacrylate (PMMA) substrate was improved by prior treatment with an acryloxypropyl trimethoxysilane-based agent. Titanium dioxide coatings were obtained by spray-coating substrates with or without prior treatment. Structure was investigated using IR, SEM, and an EPMA. Effect on durability against brushing was determined with a brush-wear test machine utilizing a commercial denture brush.A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…per day for one year [8]. Based on this finding, we conclude showed that this titanium dioxide coating has sufficient durability under conditions associated with the long term use of dentures.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…per day for one year [8]. Based on this finding, we conclude showed that this titanium dioxide coating has sufficient durability under conditions associated with the long term use of dentures.…”
supporting
confidence: 56%
“…The titanium dioxide coating on acrylic resin denture bases improves wettability, reduces adhesion of food bolus [6], and suppresses adhesion of bacteria and fungi [7]. We have reported that the use of a primer agent, which primarily consists of acryloxypropyl methoxysilane, for pre-treatment of the titanium dioxide coating affords durability of the titanium dioxide coating against brushing [8]. Moreover, the biocompatibility of a primer agent and TiO 2 coating agent has been already demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%
“…We followed the same protocol of the previous study, which assessed the durability of a titanium oxide (TiO 2) coating on PMMA 22) . The loading force of 2.94 N and gliding speed of 150 cycles per 60 s were determined by averaging the loading force and gliding speeds applied by five healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The brush was fixed with a clasp and positioned vertically to the surface of the specimens. The brush was applied at a force of 2.94 N. The gliding speed of the device was set to 150 cycles per 60 s 22) . After 600 cycles of the brush-wear test, the contact angles of the worn specimens were measured following the same protocol described above.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The high photocatalytic and superhydrophilic effects of titanium dioxide (TiO 2 ) have been reported, and when applied to dentures, they can be cleaned simply by rinsing in water. [4][5][6][7] Two methods have been proposed for the application of TiO 2 to the denture base. One method is to mix TiO 2 with resin.…”
mentioning
confidence: 99%